Pentadecapeptide BPC 157, in Clinical Trials as a Therapy for Inflammatory Bowel Disease (PL14736), Is Effective in the Healing of Colocutaneous Fistulas in Rats: Role of the Nitric Oxide-System - Robert Klicek; Marko Sever; Bozo Radic; Domagoj Drmic; Ivan Kocman; Ivan Zoricic; Tihomir Vuksic; Mihovil Ivica; Ivan Barisic; Spomenko Ilic; Lidija Berkopic; Hrvoje Vrcic; et al. (Elsevier, 2008)
We focused on the therapeutic effect of the stable gastric pentadecapeptide BPC 157 and how its action is related to nitric oxide (NO) in persistent colocutaneous fistula in rats (at 5 cm from anus, colon defect of 5 mm, skin defect of 5 mm); this peptide has been shown to be safe in clinical trials for inflammatory bowel disease (PL14736) and safe for intestinal anstomosis therapy. BPC 157 (10 μg/kg, 10 ng/kg) was applied i) in drinking water until the animals were sacrificed at post-operative day 1, 3, 5, 7, 14, 21, and 28; or ii) once daily intraperitoneally (first application 30 min following surgery, last 24 h before sacrifice) alone or with NG-nitro-L-arginine methyl ester (L-NAME) (5 mg/kg), L-arginine (200 mg/kg), and their combinations. Sulphasalazine (50 mg/kg) and 6-α-methylprednisolone (1 mg/kg) were given once daily intraperitoneally. BPC 157 accelerated parenterally or perorally the healing of colonic and skin defect, leading to the suitable closure of the fistula, macro/microscopically, biomechanically, and functionally (larger water volume sustained without fistula leaking). L-NAME aggravated the healing failure of colocutaneous fistulas, skin, and colon wounds (l-NAME groups). l-Arginine was effective only with blunted NO generation (l-NAME + l-arginine groups) but not without (l-arginine groups). All of the BPC 157 beneficial effects remained unchanged with blunted NO-generation (l-NAME + BPC 157 groups) and with NO substrate (l-arginine + BPC 157 groups) as well as l-NAME and l-arginine co-administration (L-NAME + l-arginine + BPC 157 groups). Sulphasalazine was only moderately effective, and corticosteroid even had an aggravating effect. Keywords:: stable gastric pentadecapeptide BPC 157, colocutaneous fistula, skin defect, colon defect